Parental Divorce: Challenges and Opportunities for Adolescent - Basalamah, Humaira; Pebriani, Lucia Voni (Journal of Family Sciences, 2024)
Divorce can have a significant impact on family dynamics. Adolescents with divorced parents show unique characteristics as they navigate the transition to adulthood and adjust to altered family dynamics. This study aims to see how the post-divorce parenting impacts on adolescents. The research used convenience sampling to select four adolescents with divorced parents as participants. Parenting is viewed based on the pattern of parental responsiveness and demandingness in adolescents. The data collection process was done using a qualitative approach, which involved interviews with four research participants. The interview data were then processed using thematic analysis, yielding several themes presented descriptively to answer the research questions. The results of this study found that adolescents with divorced parents have positive and negative experiences, meanings, and impacts from their parents' divorce. This is significantly influenced by the role of parents in parenting their teenagers after divorce. Parents can be risk factors and protective factors for adolescents whose parents are divorced. This study's data is crucial for divorced or divorcing parents and the Indonesian government, especially religious courts, as it provides psychoeducation on the impact of parental divorce on adolescents and the importance of appropriate post-divorce parenting.